Facetas do quotidiano burguês no Portugal de oitocentos - Cruz, Maria Antonieta (2003)
The material wellbeing and the different aspects of daily life are elements that help us distinguish the bourgeoisie from the rest of the population. By exploring the streets and houses and examining the household organisation (furniture, house fabrics and appliances, clothes, books and musical instruments, etc.), it is our objective to underline the differences between social groups. The use and the particular importance of such aspects of daily life reflect those differences. Our aim is to elaborate a summary of the results already achieved and outline the main objectives of this research work.